2020
DOI: 10.1007/s11104-020-04529-w
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of plant current pathways for non-invasive root Phenotyping using a newly developed electrical current source density approach

Abstract: Aims The flow of electric current in the root-soil system relates to the pathways of water and solutes, its characterization provides information on the root architecture and functioning. We developed a current source density approach with the goal of non-invasively image the current pathways in the root-soil system. Methods A current flow is applied from the plant stem to the soil, the proposed geoelectrical approach images the resulting distribution and intensity of the electric current in the root-soil syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 57 publications
3
49
0
Order By: Relevance
“…For partial irrigation, roots are likely more conductive than the surrounding soil, and the current flows preferentially through the roots. In the case of full irrigation, the surrounding soil is more conductive than the root, and the current is expected to leave the root system near the stem-soil interface, as also suggested by Urban, Bequet, and Mainiero (2011) and Peruzzo et al (2020). Thus, the success of the MALM method depends on the contrast between the electrical properties of the root and that of the soil and on the contact resistance at the interface between the two.…”
Section: Malm Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…For partial irrigation, roots are likely more conductive than the surrounding soil, and the current flows preferentially through the roots. In the case of full irrigation, the surrounding soil is more conductive than the root, and the current is expected to leave the root system near the stem-soil interface, as also suggested by Urban, Bequet, and Mainiero (2011) and Peruzzo et al (2020). Thus, the success of the MALM method depends on the contrast between the electrical properties of the root and that of the soil and on the contact resistance at the interface between the two.…”
Section: Malm Methodsmentioning
confidence: 94%
“…Measurement setups involving stem injection ( Figure 2) of current as a means of characterizing root systems have com-monly been used in a range of studies reviewed above. Although they adopted different methods such as ERM (Cao et al, 2010), ECM (Dietrich et al, 2012;Kendall, Pederson, & Hill, 1982), MALM (Mary et al, 2019;Peruzzo et al, 2020), EIM (Čermák et al 2013;Urban et al, 2011), and EIS (Repo et al, 2005;Repo et al, 2012), it is interesting to note that all studies share a common conclusion. Proximal leakage of current at the stem-soil and solution interface appears as a common challenge in all measurement setups involving the stemroot-soil continuum.…”
Section: Joint Discussion Of Stem Injection Methodsmentioning
confidence: 99%
“…For example, fiber‐optic distributed sensors can now autonomously measure temperature and strain with very high spatiotemporal resolution in terrestrial and aquatic systems (Ajo‐Franklin et al, 2017; Joe, Yun, Jo, Jun, & Min, 2018; Slater et al, 2010), and fiber‐based approaches for sensing chemical and biological properties are in development (Ding et al, 2015; Lu, Thomas, & Hellevang, 2019). New sensing strategies are being tested to noninvasively monitor active plant‐root functions in situ (Benjamin et al, 2020; Peruzzo et al, 2020) and to monitor nutrient fluxes (MacDonald, Levison, & Parker, 2017). Autonomous unmanned aerial vehicles (UAVs) equipped with various instruments can now sense previously difficult‐to‐reach environments in high‐resolution.…”
Section: Emerging Technologies Poised To Advance Watershed Hydrobiogementioning
confidence: 99%
“…The availability of these data and tools is enabling a new paradigm wherein data-driven methods are being used to probe hydrobiogeochemical scaling, similarity and function, as well as to generate and test new hypotheses (Peters-Lidard et al, 2017). Classical methods, such as statistical time-series analyses and concentrationdischarge relationships, are being applied to large, regional data products to determine streamflow and water quality trends across catchments with different characteristics (Godsey, Hartmann, & Kirchner, 2019;Murphy & Sprague, 2019).…”
Section: Watershed Data Cyberinfrastructure and Informaticsmentioning
confidence: 99%
“…Conceptual models consider the roots to be imperfect cylindrical capacitors, in which the amount of electric charge stored by the polarizable membrane dielectrics depends on the root-soil interfacial area (Dalton, 1995). Even though some of the underlying biophysical principles are still unclear and there are uncertainties about the relative contribution of proximal and distal (fine) roots to the magnitude of the C R detected (Dietrich et al, 2012;Ellis et al, 2013;Cseresnyés et al, 2020;Peruzzo et al, 2020), several pot and field trials have convincingly demonstrated the efficiency of the capacitance method (Středa et al, 2020). One advantage of the technique is that, as the C R value is affected not only by the size but also by the histological properties of the roots (e.g.…”
Section: Introductionmentioning
confidence: 99%